Longitudinal passive cough monitoring and its implications for detecting changes in clinical status. Issue 2 (16th May 2022) - Gabaldón-Figueira, Juan C.; Keen, Eric; Rudd, Matthew; Orrilo, Virginia; Blavia, Isabel; Chaccour, Juliane; Galvosas, Mindaugas; Small, Peter; Grandjean Lapierre, Simon; Chaccour, Carlos
Research question: What is the impact of the duration of cough monitoring on its accuracy in detecting changes in the cough frequency? Materials and methods: This is a statistical analysis of a prospective cohort study. Participants were recruited in the city of Pamplona (Northern Spain), and their cough frequency was passively monitored using smartphone-based acoustic artificial intelligence software. Differences in cough frequency were compared using a one-tailed Mann–Whitney U test and a randomisation routine to simulate 24-h monitoring. Results: 616 participants were monitored for an aggregated duration of over 9 person-years and registered 62 325 coughs. This empiric analysis found that an individual's cough patterns are stochastic, following a binomial distribution. When compared to continuous monitoring, limiting observation to 24 h can lead to inaccurate estimates of change in cough frequency, particularly in persons with low or small changes in rate. Interpretation: Detecting changes in an individual's rate of coughing is complicated by significant stochastic variability within and between days. Assessing change based solely on intermittent sampling, including 24-h, can be misleading. This is particularly problematic in detecting small changes in individuals who have a low rate and/or high variance in cough pattern. When compared to continuous monitoring, limiting observation to 24 h can lead to inaccurate estimates of change in cough frequency, influenced by its mean frequency and variance. This is important when evaluating small changes in cough frequency. https://bit.ly/3NtfPw1